Everyone knows but you [large type] : a tale of murder on the Maine coast - Ricks, Thomas E. (Center Point Large Print, 2024)
"After his wife and two children are killed in a car crash, Ryan Tapia starts a new life in Maine. But his first case there is a puzzling oddball -- the corpse of a fisherman washes up on federal land, while the man's boat drifts into waters that are part of an Indian reservation. Ryan quickly learns the nuances of Maine life as he delves into two illicit coastal trades: hard drugs and rare fish. Many of the locals are happy to see that particular fisherman dead. What's more, they are not shy about noting that Ryan must have screwed up pretty badly to be posted to such a remote location as Bangor, Maine. Undaunted, Ryan works to understand the unforgiving way of life on Liberty Island, where people live by an older, harsher code. Adrift on a sailboat one day, he encounters a man from the Malpense tribe, living as a hermit on a remote island, who witnessed something that fateful day."--